Development of technology and quality control of suspension for comprehensive therapy of mastopathy - Zujkina, S; Vishnevska, L; Kovaliova, T; Shtuchna, N; Khalavka, M (Annals of Mechnikov's Institute, 2021)
Mastopathy is a common disease of the mammary gland. According to a number of researchers, various forms (about 50 of them) occur in 20-60% of women over 30 years of age. The peak incidence occurs at 45 years. Mastopathy is a disease which is typical in women of reproductive age – from 25 to 45 years. In most cases, after the onset of menopause, all signs of the disease disappear. Mastopathy does not always lead to irreversible changes. However, against the background of benign breast diseases, breast cancer occurs 3-5 times more often, and in some forms of mastopathy even 25-30 times. The aim of the work was to develop the composition and technology of extemporaneous suspension for complex pharmacocorrection of mastopathy and prevention of breast cancer. The methods of literary analysis, marketing research, pharmacotechnological and physicochemical research methods were used in the work. The obtained results indicate that the developed suspension is sedimentationally and aggregatively stable, pH is in the range of 5.5–6.0. Qualitative and quantitative indicators do not change during storage. The shelf life of the extemporaneous suspension is 12 days at a temperature of (25 ± 2) ° C. Key words: mastopathy, breast cancer, extemporaneous suspension. Funded by the Ministry of Health of Ukraine at the expense of the state budget in the theme “Development of monographs of the State Pharmacopoe-ia of Ukraine for compounding medicines” framework (state registration number: 0120U102430) DOI: 10.5281/zenodo.5761131